(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Aim: The aim of this study was to assess the effect of preheating on the surface microhardness of different commercially available composite resins (G-aenial, Filtek Z350 and Tetric-N-Ceram). Materials and Methods: Tubes of the composite resins were either kept at room temperature (24 ±10 C) or preheated for 40 min in a commercially preheating device to 40 0 C, 50 0 C and 60 0C, respectively. From composite resin tubes, a total of 120 disk-shaped specimens (40 specimens of each composite resin, 10 disks from each temperature setting) were prepared by inserting uncured preheated composite resin into cylindrical nylon moulds (5 mm diameter × 2 mm height); before light polymerized for 40s with a light emitting diode curing unit. The Vicker’s microhardness number (VHN) of each specimen was measured. Two-way ANOVA and Tukey test were used to analyze the collected data at a significance level of 0.05. Results: In comparison to the room temperature, there was a significant increase in the mean VHNs of each composite resin by preheating to 40 0C, 50 0 C and 60 0 C, respectively (p<0.05). For G-aenial posterior, Filtek Z350XT and Tetric-N-Ceram, at room temperature, the mean VHNs were 51± 4.3, 60.6± 3.7 and 76.6±1.4, respectively with significant difference between G-aenial posterior and Tetric-N-Ceram (p<0.05), while at 400C, the mean VHNs were 65.7±2.5, 86.8±2.3 and 88.4±1.8, respectively with significant differences (p<0.05) between G-aenial posterior and the other two composites. At 500C, the mean VHNs were 109.4±0.9, 104.4±3.4 and 114±0.71, respectively with no significant difference between composite resins. At 600C, the mean VHNs were 122±3.2, 129±3.4 and 136±2, respectively with significant difference between G-aenial posterior and Tetric-N-Ceram (p<0.05). Conclusions: Preheating significantly increased the surface microhardness of all tested composite resins with the highest value observed for Tetric N-Ceram at 600C preheating temperature.